TAT-apoptosis repressor with caspase recruitment domain protein transduction rescues mice from fulminant liver failure - An, Junfeng; Harms, Christoph; Lättig-Tünnemann, Gisela; Sellge, Gernot; Mandić, Ana D.; Malato, Yann; Heuser, Arnd; Endres, Matthias; Trautwein, Christian; Donath, Stefan (Hepatology (Baltimore, Md.), 2012)
Acute liver failure (ALF) is associated with massive hepatocyte cell death and high mortality rates. Therapeutic approaches targeting hepatocyte injury in ALF are hampered by the activation of distinct stimulus‐dependent pathways, mechanism of cell death, and a limited therapeutic window. The apoptosis repressor with caspase recruitment domain (ARC) is a recently discovered death repressor that inhibits both death receptor and mitochondrial apoptotic signaling. Here, we investigated the in vivo effects of ARC fused with the transduction domain of human immunodeficiency virus 1 (HIV‐1) (TAT‐ARC) on Fas‐ and tumor necrosis factor (TNF)‐mediated murine models of fulminant liver failure. Treatment with TAT‐ARC protein completely abrogated otherwise lethal liver failure induced by Fas‐agonistic antibody (Jo2), concanavalin A (ConA), or D‐galactosamine/lipopolysaccharide (GalN/LPS) administration. Importantly, survival of mice was even preserved when TAT‐ARC therapy was initiated in a delayed manner after stimulation with Jo2, ConA, or GalN/LPS. ARC blocked hepatocyte apoptosis by directly interacting with members of the death‐inducing signaling complex. TNF‐mediated liver damage was inhibited by two independent mechanisms: inhibition of jun kinase (JNK)‐mediated TNF‐α expression and prevention of hepatocyte apoptosis by inhibition of both death receptor and mitochondrial death signaling. We identified JNK as a novel target of ARC. ARC's caspase recruitment domain (CARD) directly interacts with JNK1 and JNK2, which correlates with decreased JNK activation and JNK‐dependent TNF‐α production. Conclusion: This work suggests that ARC confers hepatoprotection upstream and at the hepatocyte level. The efficacy of TAT‐ARC protein transduction in multiple murine models of ALF demonstrates its therapeutic potential for reversing liver failure. (HEPATOLOGY 2012)